Reversible Cortical Visual Impairment in an Adolescent Due to a Posterior Fossa Arachnoid Cyst: A Case Report - Jelena Škunca Herman; Dario Josip Živković; Ivana Orešković; Lana Knežević; Maja Malenica Ravlić; Blanka Doko Mandić; Goran Marić; Ante Vukojević; Hrvoje Sliepčević; Mia Zorić Geber; Vladimir Kalousek; Zoran Vatavuk (Life, 2025)
Background: Arachnoid cysts are typically benign and asymptomatic, but large cysts can exert a mass effect on adjacent neural structures. Based on the available literature, no cases of cortical visual impairment (CVI) in an adolescent caused by posterior fossa arachnoid cysts have been reported. Case presentation: We report the case of a previously healthy 16-year-old girl who presented with sudden and rapidly progressive bilateral visual loss due to a large retrocerebellar arachnoid cyst. She reported blurred vision, tunnel vision-like, and decreased visual acuity. Although neuro-ophthalmologic and imaging workup revealed no damage to the anterior visual pathways, she exhibited progressive visual decline. Functional tests confirmed bilateral cortical visual impairment: pattern-reversal visual evoked potentials (VEPs) showed preserved and symmetric P100 latencies and amplitudes, while automated perimetry revealed bilateral concentric visual field constriction with preserved central islands. Following cystoperitoneal drainage, her vision rapidly and completely recovered. Conclusions: To the best of our knowledge, this is the first reported case of reversible CVI in an adolescent caused by a posterior fossa arachnoid cyst without intracranial pressure (ICP) elevation or optic nerve involvement, and with tunnel vision-like. Our findings emphasize the role of posterior fossa lesions in visual dysfunction and highlight the potential reversibility of cortical visual loss when timely decompression is achieved. This case underscores the importance of including posterior fossa lesions in the differential diagnosis of unexplained bilateral visual loss, even in the absence of elevated intracranial pressure or anterior visual pathway involvement.